Sulfur Enhancement for the Improvement of Castor Bean Growth and Yield, and Sustainable Biodiesel Production - Mukhtar, Ahmed; Awan, Masood Iqbal; Sadaf, Sana; Mahmood, Athar; Javed, Talha; Shah, Adnan Noor; Shabbir, Rubab; Alotaibi, Saqer S.; Shah, Anis Ali; Adamski, Robert; Siuta, Dorota (Frontiers in Plant Science, 2022)
Due to limited conventional energy sources, there is a need to find substitute, non-conventional sources of energy to meet the societal demands on a sustainable basis. Crude oil and edible oil remain major import items in Pakistan, the deficit of which can be compensated by using biomass, preferably inedible oilseeds. Therefore, the current study evaluated the role of sulphur (S) fertilization for improving yield (seed and oil), and biodiesel value of castor bean that is a potential inedible crop with minimum input requirements. For this purpose, a combined approach of field experimentation and lab analysis was conducted to explore the potential of two castor bean cultivars (DS-30 and NIAB Gold) against four S supply rates viz. 0, 20, 40, and 60 kg S ha−1 in terms of growth, phenology, and yield parameters. Subsequently, the obtained seed samples were analyzed for biodiesel related parameters in the Bio-analytical Chemistry lab, Punjab Bio-energy Institute, Faisalabad. The incremental S rates increased seed yield for both cultivars and the highest yield was recorded at 60 kg S ha−1 for NIAB Gold. For NIAB Gold, the oil content increased by 7% with S fertilization at 60 kg ha−1, and for DS-30, the oil content increased by 6% at 60 kg ha−1. As with incremental S fertilization, the oil yield increased on hectare basis, the quantity of produced biodiesel also increased. Importantly, the tested quality parameters of biodiesel except biodiesel viscosity were in ASTM standard range. Overall, it has been concluded that castor bean is a promising and sustainable option for producing biodiesel as it is non-competitive to food crops and requires little inputs.